1981
DOI: 10.1042/bj2000069
|View full text |Cite
|
Sign up to set email alerts
|

Difluoromethylornithine irreversibly inactivates ornithine decarboxylase of Pseudomonas aeruginosa, but does not inhibit the enzymes of Escherichia coli

Abstract: DL-alpha-Difluoromethylornithine, an enzyme-activated irreversible inhibitor of eukaryotic ornithine decarboxylase and consequently of putrescine biosynthesis, inhibited ornithine decarboxylase in enzyme extracts from Pseudomonas aeruginosa in a time-dependent manner t1/2 1 min, and also effectively blocked the enzyme activity in situ in the cell. Difluoromethylornithine, however, had no effect on the activity of ornithine decarboxylase assayed in enzyme extracts from either Escherichia coli or Klebsiella pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…In two separate cultures the uninduced Datura ODC activity was also approximately 5-fold higher than in the control cells. Further evidence that the increased ODC activity was from the Datura cDNA was provided by the sensitivity of the Datura ODC activity to the presence of 1.0 mM DFMO, whereas the background activity represented by the endogenous E. coli ODC was resistant to DFMO as previously described [37].…”
Section: Expression Of Datura Odc In E Colimentioning
confidence: 69%
See 1 more Smart Citation
“…In two separate cultures the uninduced Datura ODC activity was also approximately 5-fold higher than in the control cells. Further evidence that the increased ODC activity was from the Datura cDNA was provided by the sensitivity of the Datura ODC activity to the presence of 1.0 mM DFMO, whereas the background activity represented by the endogenous E. coli ODC was resistant to DFMO as previously described [37].…”
Section: Expression Of Datura Odc In E Colimentioning
confidence: 69%
“…The black circle marks the Lys shown to be the main PLP-binding site and the black square marks the Cys shown to be the DFMO binding site in the mouse ODC [12]. The black triangle marks the cleavage site for the processing of the oat ADC [37] and the underlined sequence is the motif resembling a sequence conserved in methyltransferases and spermidine synthases. Only the DapDC with the greatest similarity to the Datura ODC is presented.…”
Section: Tabacimentioning
confidence: 99%
“…Addition of DL-a-difluoromethyl arginine, a compound known to be an irreversible specific inhibitor of ADC (17), caused a 65% inhibition at 50 ,M, and at 0.5 mm the compound almost completely abolished the decarboxylation. However, addition of 1 mM DL-a-difluoromethyl ornithine, which is known to be a specific inhibitor of ODC activity (16), had no effect. This implies that the decarboxylation observed in this reaction is solely due to the ADC activity.…”
Section: Resultsmentioning
confidence: 92%
“…First, added [U-'4C]ornithine is readily converted into Put without lag period (Fig. 5) (19,25) and arginine decarboxylase (20), respectively, for determination of whether Put could be formed from decarboxylation of arginine in the aleurone layers have been unsuccessful (Fig. 6).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of effects of the inhibitors on Put formation could be due to poor uptake of the chemicals or lack of sensitivity of the decarboxylases of barley aleurone layers to the chemicals. It has been reported that not all of the ornithine decarboxylases isolated from bacteria (19) and plant tissues (15) are DFMO sensitive.…”
Section: Methodsmentioning
confidence: 99%